Cavitation-enhanced transdermal vaccine delivery by ultrasound - Bhatnagar, S (2014)
Currently, the most common route for vaccine delivery is by intramuscular injection with a needle and syringe. Injection has number of disadvantages, such as risk of infection at the i njection site, needle prick injuries, and needle phobia that leads to significant levels of patient non-compliance. Therefore, the focus of this thesis is the development of an alternative ultrasound-assisted transdermal vaccine delivery system. To do so, we target immunological Langerhans cells in the epidermal layer of the skin that efficiently provoke an immune response. The stratum corneum (SC) is a barrier that prevents conventional transdermal vaccine delivery. Methods such as microneedles, iontophoresis and thermal ablation are presented in literature for the permabilisation of this layer. Sonophoresis is the use of ultrasound to transport molecules through a medium. Previous studies have demonstrated that the key underpinning mechanism is inertial cavitation, which leads to permeabilisation of the SC and facilitates transdermal delivery. Most studies to date have pre-exposed the skin to ultrasound prior to delivery of a vaccine in liquid form as a droplet placed on the skin. This approach is not practical for widespread use, but more importantly fails to take advantage of the potential of cavitation-mediated micro streaming to enhance active transport of molecules beyond the permeabilised skin. The focus of the present work is the development of a complete system that enables storage of the vaccine in a readily useable gel form whilst promoting and monitoring cavitation activity to simultaneously permeabilise the skin and enhance transdermal vaccine transport. Through initial in vitro studies, we first demonstrated that inertial cavitation can be exploited to promote the active transport of molecular entities such as vaccine molecules from a gel into a biological medium. A gel vaccine dosage formulation is utilised in order to mimic current clinically approved and established clinical ultrasound coupling gel formulations. By comparing the effects mediated at two ultrasound frequencies (0.256 MHz vs 1 MHz) which preferentially promote cavitational microstreaming or acoustic streaming, ultrasound parameters most conducive to producing high levels of inertial cavitation were identified as 0.256 MHz and peak rarefactional pressures on the order of 1 MPa. Three vaccine loaded gels were then formulated with either micro- or nano-sized cavitation nuclei and assessed for the optimal acoustic and chemical characteristics at the predetermined ultrasound parameters. Nano-sized nuclei were shown to be most effective at lowering the inertial cavitation threshold, as well as instigating the highest and most sustained levels of inertial cavitation as indicated by broadband acoustic emissions at the ultrasound focus, without causing any structural damage to the vaccine molecules themselves. Ex vivo data has shown that nanoscale-nucleated inertial cavitation at the skin surface delivered a model vaccine Ovalbumin (OVA) to depths of 500 μm into porcine skin. Novel nanoparticles produced in-house used to enhance and instigate cavitation at lower pressures penetrated to depths of up to 700 μm, due to their small size and unique ability to self-propel. Delivery profiles were obtained using multi-photon microscopy of skin sections immediately after treatment. Analysis of acoustic emissions from the focus showed substantial correlation between high delivery dose and depth, and significant amounts of inertial cavitation (i.e. broadband acoustic emissions from the focus). In vivo studies showed that the delivery achieved to murine skin was significantly (p<0.05) higher in the nanoparticle-assisted ultrasound transdermal vaccination group than the chemical penetration enhancer (positive control) group, with delivery of doses up to 1 μg /treatment, compared to 400 ng in the positive control group. This dose was sufficient to trigger an antigen-specific immune response. Specific anti-OVA IgG antibody levels in the ultrasound-assisted vaccine delivery group were significantly (p<0.05) higher than in all other control groups, and substantially higher than the current gold standard in transdermal delivery – chemical penetration enhancers. Although a low level antibody response was observed transdermally compared to the subcutaneous injection group (indicative of 100% delivery response), it is believed that optimisation of this system will lead to a viable and non-invasive delivery platform for vaccines that can be used both in a primary care setting, and eventually for self-vaccination at home.